A comparative study of magnetic resonance imaging on the gray matter and resting‐state function in prodromal and first‐episode schizophrenia. Issue 6 (14th August 2018) - Lian, Nan; Lv, Hailong; Guo, Wenbing; Shen, Yidong; Wu, Renlong; Liu, Yong; Zhu, Furong; Hu, Maorong; Ou, Jianjun; Zhao, Jingping
Abstract : It is very difficult to predict the future development possibility of schizophrenia through the clinical symptoms of the high‐risk cases. Therefore, how to determine the possibility of developing into schizophrenia individuals before the onset of the diseases are particularly important. The study investigated cerebral gray matter volume differences and resting‐state functional connections among patients with psychosis risk syndrome (PRS), patients with first‐episode schizophrenic (FES), and healthy controls (HC), aiming to provide scientific clinical evidence for schizophrenia early identification and intervention. A total of 19 PRS patients, 18 FES patients, and 29 HC were recruited. Gray matter volume and amplitude of low‐frequency fluctuation (fALFF) during resting‐state functional studies were measured. Comparison of gray matter volumes showed that PRS and FES groups had common reduced gray matter volume in the right caudate. PRS and FES patients showed altered connectivity mainly in the semantic processing‐related brain areas. fALFF analysis found that PRF and FES patients had significant differences in fALFF values of the brain region mainly located in the subcortical network, visual recognition network, and auditory network. In addition, PRF individuals had a higher fALFF value and a lower fALFF value in the anterior wedge of the cerebral network than the HC group. Gray matter volume loss between related brain areas might appear prior to illness onset. Similar fALFF values occurred in PRS and FES groups indicated that multiple brain regions of neuronal activity abnormalities and unconventional neural network mechanism have been existed in PRS patients.